2001
DOI: 10.1046/j.1432-1327.2001.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Ets1 is a common element in directing transcription of the α and β genes of human protein kinase CK2

Abstract: Protein kinase CK2 is a conserved and vital Ser/Thr phosphotransferase with various links to malignant diseases, occurring as a tetramer composed of two catalytically active (CK2α and/or CK2α′) and two regulatory subunits (CK2β). There is balanced availability of CK2α and CK2β transcripts in proliferating and differentiating cultured cells. Examination of the human CK2β gene for transcriptionally active regions by systematic deletions and reporter gene assays indicates strong promoter activity at positions −42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…ChIP analysis revealed that AR42 treatment caused a concentration-dependent increase in the association of CK2α promoter DNA with acetylated histone H3 (Fig. 4B), which in turn was associated with the enhanced recruitment of the transcription factor Ets-1, a key regulatory element of the CK2α gene (25), to the promoter, without altering the expression level of Ets-1 (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…ChIP analysis revealed that AR42 treatment caused a concentration-dependent increase in the association of CK2α promoter DNA with acetylated histone H3 (Fig. 4B), which in turn was associated with the enhanced recruitment of the transcription factor Ets-1, a key regulatory element of the CK2α gene (25), to the promoter, without altering the expression level of Ets-1 (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that relevant promoter regions of CK2a, CK2b genes are located within a few hundred base pairs upstream of the transcription start sites. In most of the experiments, even smaller DNA fragments were used for the analysis of transcriptional control [18,56]. Interestingly, the CK2a gene is organized with the first exon located over 35 kb upstream of the second exon, which harbors the start codon.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we conclude that SP1 is not the transcription factor which is activated by CK2 for the regulation of the CK2 gene expression. Ets1 is another transcription factor which is supposed to bind to the CK2a promoter [56]. So far, it is not known whether Ets1 is a substrate for CK2.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that CK2 is involved in cell cycle progression and while it is known that all CK2 subunits are expressed throughout the cell cycle, relatively little is known about how either CK2α or CK2β expression is regulated 72 . Characterization of both the CK2α and CK2β genes, as well as adjacent upstream sequences led to identification of a pair of highly conserved Ets1 response elements 73 , 74 . While these observations offer an attractive mechanism for the coordinated expression of CK2 subunits destined to form tetrameric complexes, these results are not entirely consistent with earlier studies that had shown that CK2β protein was synthesized in excess of the catalytic subunit in exponentially growing tissue culture cells 75 .…”
Section: Challenges To the Traditional View Of Ck2mentioning
confidence: 99%